Learning maths for kids: how to garner their attention! / Yusrina Andu - Andu, Yusrina (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Undoubtedly, mathematics is crucial in our daily life. Even toddler needs it for cognitive development especially when it comes to counting numbers, as well as simple addition and subtraction for ages between 5 and 7 years old. It seems easy, but the acceptance of the learning varies on how they learn it. The information gained needs to be digested by the kids before they fully understand. The main concern is how much input they would receive from the learning process. Several strategies were made and are in progress to ensure the knowledge can reach them and are on par with their age. Presume that the kids who could not understand are not that poor. What if the method used to coach them is not an approachable way? Here the experiment begins. As teachers/parents, we should realise the behaviour of our kids.